Understanding Interpretations of and Responses to Childhood Fever in the Chikhwawa District of Malawi - Ewing, Victoria L.; Tolhurst, Rachel; Kapinda, Andrew; SanJoaquin, Miguel; Terlouw, Dianne J.; Richards, Esther; Lalloo, David G. (Public Library of Science, 2015)
Universal access to, and community uptake of malaria prevention and treatment strategies are critical to achieving current targets for malaria reduction. Each step in the treatment-seeking pathway must be considered in order to establish where opportunities for successful engagement and treatment occur. This article describes local classifications of childhood febrile illnesses, present an overview of treatment-seeking, beginning with recognition of illness, and suggests how interventions could be used to target the barriers experienced.